Application of Poloxamer for In Situ Eye Drop Modeling by Enrichment with Propolis and Balsam Poplar Buds Phenolic Compounds - Monika Jokubaite; Mindaugas Marksa; Kristina Ramanauskiene (Gels, 2024)
In situ poloxamer-based gels are increasingly being explored as ocular drug delivery carriers to extend the release of active substances, thereby enhancing bioavailability. The objective of this study was to develop thermally stable in situ gels incorporating balsam poplar bud extract, propolis extract, and p-coumaric acid solution and to evaluate the physicochemical parameters of these gelified eye drops. This research assessed the compatibility of poloxamer-based eye drops with active components, their physicochemical properties, stability post-sterilization and during storage, and the release profiles of the active compounds. Fifteen eye drop formulations were prepared and categorized into three groups based on active components. One of the active components was propolis extract. As an alternative to propolis, eye drops containing the plant precursor, balsam poplar bud extract, were developed. The third group’s active component was p-coumaric acid, a dominant phenolic acid in propolis and balsam poplar bud extracts. The study reported phenolic contents of 76.63 CAE mg/g for propolis and 83.25 CAE mg/g for balsam poplar bud aqueous extracts, with balsam poplar bud extracts showing higher SPF values (14.0) compared to propolis (12.7), while p-coumaric acid solution exhibited the highest SPF values (25.5). All eye drops were transparent, with pH values meeting the requirements for ocular drops. Formulations containing 8–10% poloxamer 407 met the criteria for in situ gels. All formulations remained stable for 90 days. Conclusion: The study results indicate that the formulated gels possess suitable physicochemical properties, are resistant to applied autoclaving conditions, and exhibit an extended release of active compounds with an increase in poloxamer content.